Active herpesviruses are associated with intensive care unit (ICU) admission in patients pulmonary infection and alter the respiratory microbiome - Liu, Zhiguang; Qi, Chun-jian; Shi, Yujia; Li, Tianyu; Fang, Yuan; Zhang, Qian (Frontiers in Microbiology, 2024)
The Herpesviridae family contains several human-related viruses, which are able to establish colonizing and latency in the human body, posing a significant threat to the prognosis of patients. Pulmonary infections represent one of the predominant infectious diseases globally, characterized by diverse and multifaceted clinical manifestations that have consistently attracted clinician's concern. However, the relationshipimpact of herpesviruses on the prognosis of individuals with pulmonary infections and the respiratory microbiota remains poorly understood.Methods: Here, we retrospectively analyzed respiratory samples from 100 patients with pulmonary infection detected by metagenomic next-generation sequencing (mNGS).Results: Employing mNGS, sixfive herpesvirus species were detected: Human alphaherpesvirus 1 (HSV-1), Human gammaherpesvirus 4 (EBV), Human betaherpesvirus 5 (CMV), Human betaherpesvirus 7 (HHV-7), and Human betaherpesvirus 6B (HHV-6B). These viruses exhibited high detection frequency in ICU patients and were significantly associated with patients' ICU admission rates and total hospital stays. Regression analysis showed that the age and positivity of herpesviruses in patients were independently correlated with ICU admission rates. In addition, positivity of herpesvirus was related with increased ICU days and total hospital stay. Moreover, tThe herpesvirus-positive group demonstrated markedly higher incidences of co-infections and fungipositivefungal detections, predominantly involving Pneumocystis jirovecii and Aspergillus fumigatus. Analysis of respiratory microbiota revealed a substantially altered community composition within the herpesvirus-positive group, and herpesviruses were significantly positively correlated with the diverse respiratory opportunistic pathogens.Overall results substantiate that the active herpesvirusesreactivation of herpesviruses in patients with pulmonary infections was were significantly associated with high ICU admission ratepoor prognosis. Moreover, the herpesviruses promotes the dysbiosis of the respiratory microbiota and an increased proportion of co-infections may be pivotal factors contributing to this phenomenon. These insights could contribute to unraveling the underlying mechanisms connecting active herpesvirusesherpesviruses reactivation to the progression of severe illnesses.